(untitled) (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2019)
The neoliberal capitalism as an economic system has extended its reach to a point where it determines the individuals’ gather and relate to each other; it present itself as a voracious system that ends up by hoarding any social manifestation which in principle would appear to be opposite or as an alternative, going through another way; nevertheless it is grasped, included and manipulated by said system, achieving banalization or deactivating the political and social power it could contain, converting it into a consumable and rentable proposal. Diverse allies of neoliberal capitalism allow it to strengthen and transmit its logic whose goal is consumism. The mass media are an undeniable mean for this task; they allow to rapidly reach to a great amount of people and position an event by making it news and, now with social media, converting it into a trending topic.So much so that what may represent the other, becomes a good object to exploit and commodify. Growing reality shows. The televised difference. This happens with the recent appearance of Yalitza Aparicio, oaxacan indigeneous woman starring the widely awarded movie of Alfonso Cuarón: Roma. The intention that matters here is not the critic to Yalitza acting, nor comment on how good or bad is her appearance in the movie, neither discussing if she deserved winning the Oscar. It is without a doubt worth mentioning the effort she put at so many levels and she deserves recognition and the signs of support she received. Substantially from her acting, the problematic that surrounds domestic laborers in our country is made visible as the film is a sample of the conditions and short-comings that these workers suffer. Besides being set in the decade of the seventies, the current situation remains quite similar today. It is proposed to step into the subject from a critical point of view, trying to give a reading to the phenomenon that was created after the release of the movie, from a theory that manifests the inequalities which remain latent, in parallel to an analysis from gender perspective, using concepts like consumption-society, whiteness as a racist logic, the denied identity to become part of the elite and of course, a neoliberal empowerment. The starting points are Yalitza’s photographs published in important magazines like Vanity Fair and Vogue, where she’s seen wearing garments from known designers like Louis Vuitton, Prada among others, that leads to the question: What can be the reflection upon the inclusion of Yalitza in the multi-billionaire world of Hollywood?